2016
DOI: 10.3171/2015.5.jns15299
|View full text |Cite
|
Sign up to set email alerts
|

The burden and risk factors of ventriculostomy occlusion in a high-volume cerebrovascular practice: results of an ongoing prospective database

Abstract: V entriculostomy occlusion is a common complication after external ventricular drain (EVD) placement. A review of published prospective and retrospective studies indicates that approximately 1% to 7% of EVDs require replacement secondary to occlusion. [1][2][3]5,8,9,20 Furthermore, in a Nationwide Inpatient Sample database study of more than 101,000 hospitalizations in which ventriculostomy was performed, nearly 6% of patients required at least 1 additional ventriculostomy procedure. 18Studies have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…In the current study, we failed to detect differences in the occurrence of postoperative hematoma in the two groups, and the frequency was also considerably lower than previous reports [6,9,17,18,[21][22][23]. Studies have previously reported rates of close to non-existent to approximately 40% [9,17,22].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In the current study, we failed to detect differences in the occurrence of postoperative hematoma in the two groups, and the frequency was also considerably lower than previous reports [6,9,17,18,[21][22][23]. Studies have previously reported rates of close to non-existent to approximately 40% [9,17,22].…”
Section: Discussioncontrasting
confidence: 97%
“…It is difficult to explain why there was a greater occurrence of occlusion in the tunnelated group, but this may have been associated with misplacement; in the tunnelated group, there was a trend towards fewer EVDs in optimal placement compared to the bolt group. One recent study reported that permanent catheter occlusion was however more frequently correlated to small catheter diameter and therapeutic anticoagulation, whilst a non-ideal catheter position was only marginally significant [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective database regarding EVD insertion and practice for all indications, 19% of 98 patients required at least one EVD replacement, and 41% developed at least one temporary occlusion. 46 In a retrospective analysis of 227 patients with IVH requiring EVD, large bore catheters decreased the risk of catheter obstruction without any increase in catheter-related hemorrhages, and a nonsignificant decrease in catheter-related infections was also noted. Despite this, mortality was higher in the large bore catheter group, likely due to a selection bias where patients with larger volume hematomas were selected to receive the large bore catheters.…”
Section: Brief History Of Intraventricular Thrombolyticsmentioning
confidence: 98%
“…Experimental studies of thrombolytic-mediated clot removal have consistently demonstrated improved blood clot removal, hydrocephalus, and inflammation. 45,46,[48][49][50][51] In 2000, a systematic review of 16 retrospective studies (n ¼ 201) with severe IVH (Graeb score !7) secondary to ICH reported that combined therapy with EVD placement and IVF was associated with a significantly lower mortality rate (9%) and lower risk for unfavorable outcome (22%), as compared with patients treated with EVD alone (mortality 56%; poor outcome: 87%). 40 In 2002, a Cochrane database systematic review of 10 independent studies (8 case series/ retrospective studies, 1 quasi-RCT, 1 RCT) using IVF found anecdotal evidence supporting safety and possible therapeutic value.…”
Section: Brief History Of Intraventricular Thrombolyticsmentioning
confidence: 99%
“…tion of pseudoaneurysms, 1,10,18,29 arteriovenous fistulas, 18 or intracranial hemorrhage that causes new neurological deficits. 8 Lastly, EVDs can result in local surgical-site infections or, worse, infection of the meninges, brain parenchyma, or ventricular system. 16,23 The risk factors for EVD-related infections include intraventricular hemorrhage, craniotomy, and the duration of EVD placement, with a significant increase in risk after 5 days of drainage.…”
mentioning
confidence: 99%